Public Video Surveillance and the Separation of Powers - Zhang, Lianhan (2015)
The thesis focuses on the response from the United States government on new challenges brought by the public video surveillance, in particular the privacy threat. Regarding regulating public video surveillance, the United States has gone on a different path, either from Britain with its similar political system or from China with a totally different one. The three branches of government in the U.S. are deadlocked and unable to take any meaningful actions. The Supreme Court, which is in a strong position to set national and uniform standards for privacy protection, has not found a way to break away from its own precedents. The legislative branch can do little on the national level regulations due to federalism and the distribution of law enforcement activities at the state and local level. Local legislative efforts might be helpful, but the process in each place will be complicated by concerns about public security, the interests of industry, and politicians’ imperative to take visible actions like video surveillance to fight against crimes and protect people, especially in the post-9/11 context. The executive branch might be the weakest point in the deadlock because it already bears responsibility for resolving tensions between privacy and safety. In the absence of action by the judicial and the legislative branches, self-restraint by the executive branch has become crucial in determining the actual privacy protection, however, the possibility of abuse by the executive branch may increase at the same time. Also, the United States’ local governments are not accountable to a single national authority. They must be accountable to the people. This thesis concludes that the public participation is the key to breaking through the deadlock in light of the democratic political structure in the United States